Grid parameters analysis of 11 kV radial feeder on residential areas based on forecasted emerging load: A case study of Tarkeshwor Municipality, Nepal - Pokhrel, Bidhan; Bhattarai, Nawraj; Poudyal, Ramhari; Gautam, Rupesh; Paudyal, Khem N. (Journal of Engineering Issues and Solutions, 2023)
The study focuses on the technical performance analysis of a radial distribution network in a rapidly urbanising area under the current, future, and optimised scenarios. The control area in this research is Tarkeshwor Municipality, Nepal, which lies in the outer stretch of Kathmandu, representing the urbanising loads. In this paper, the electric cooking load has been added to the long term forecasted load up to ten years from now, representing emerging technology and load that adds to the peak load in the daily load curve of the control area. The placement of reactive power suppliers (i.e. Capacitor placement) in optimal network buses is also proposed as an optimisation tool that exhibits improved power quality and reliability with the forecasted load. The peak load is found to be increased to 21.93 MVA at the tenth year’s end including targeted emerging load due to which the voltage profile also goes out of the limits. Optimal placement of capacitor on optimal buses results in improved voltage profile and also reduces active power loss of the distribution network in the control area. The analysis and discussion in this research will be helpful to the policymakers as well as the electric utility for planning the supply and utilisation pattern of electricity in the future.